Assessment of nutritional status in free-living elderly individuals by bioelectrical impedance vector analysis. - Buffa R; Floris G; Marini E (Nutrition, 2009)
OBJECTIVE: The aim of the present research was to examine bioelectrical vector changes in relation to nutritional status in a sample of healthy free-living elderly people. METHODS: The study group consisted of 170 men and women 70 to 99 y of age. Anthropometric and bioelectrical (resistance and reactance, 50 kHz, 800 muA) measurements were taken. Bioelectrical impedance vector analysis was applied. Nutritional status was determined by the Mini-Nutritional Assessment. Bioelectrical characteristics of normal and undernourished individuals were compared statistically with Hotelling's T(2) test and graphically with 95% probability confidence ellipses. RESULTS: The impedance and multidimensional approaches showed a clear association. Undernourished subjects had a smaller phase angle (men 5.2 +/- 1.3 versus 5.7 +/- 1.0 degrees, P = 0.027; women 5.0 +/- 1.0 versus 5.4 +/- 0.9 degrees, P = 0.065) than normally nourished subjects. CONCLUSION: Bioelectrical impedance vector analysis represents a promising indicator of nutritional status, suitable in screening programs and clinical practice.